2015
DOI: 10.2196/mhealth.4620
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Engaged Approach to Developing an mHealth HIV/STI and Drug Abuse Preventive Intervention for Primary Care: A Qualitative Study

Abstract: BackgroundDespite ongoing prevention efforts, HIV and other sexually transmitted infections (HIV/STIs) and drug use remain public health concerns. Urban adolescents, many of whom are underserved and racial minorities, are disproportionately affected. Recent changes in policy, including the Affordable Care Act, and advances in technology provide HIV/STI and drug abuse prevention scientists with unique opportunities to deliver mobile health (mHealth) preventive interventions in primary care.ObjectivesThe purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 26 publications
(37 reference statements)
1
57
0
Order By: Relevance
“…To guide and direct the interviews, a semi-structured thematic interview guide [40] regarding different sources of power was used. The sources of power, which were inspired from the first phase of the study [31] and aspects of empowerment derived from an empowerment program [41] were: knowledge power, skills power and personal power. …”
Section: Discussionmentioning
confidence: 99%
“…To guide and direct the interviews, a semi-structured thematic interview guide [40] regarding different sources of power was used. The sources of power, which were inspired from the first phase of the study [31] and aspects of empowerment derived from an empowerment program [41] were: knowledge power, skills power and personal power. …”
Section: Discussionmentioning
confidence: 99%
“…Data are from a larger study focused on the development and examination of a mobile-health HIV/STI and drug abuse preventive intervention (Córdova et al, 2015; Córdova et al, 2016). Data collection occurred between December 2013 and October 2014, and was approved by the University of Michigan’s Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Although preliminary analysis indicated that saturation—defined as the point at which no new information or themes related to HIV/STI communication were identified in the data (Bowen, 2008)—was reached, we conducted one additional focus group and two individual interviews. Investigators have reported saturation with three focus group (Krueger & Casey, 2014) and 4–6 individual interviews (Córdova et al, 2015; Guest, Bunce, & Johnson, 2006). Among the 29 participants, 25 participated in focus group interviews that ranged in size from 2–6 participants, and 4 participated in individual interviews.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preferred content often includes information about HIV/STIs, proper condom use, behavioral risk reduction strategies, and partner communication strategies [19,20]. For persons living with HIV/AIDS (PLHA), preferred content includes information about health care providers and treatment, especially regarding linkage and retention into care and medication adherence [21,22].…”
Section: Introductionmentioning
confidence: 99%